Jurnal Penginderaan Jauh dan Pengelolaan Data Citra Digital : Deteksi Daerah Tercemar Lumpur Asam Menggunakan Data Landsit 7 ETM Berdasarkan Suhu Permukaan Tanah - Sulma, Sayidah, Pasaribu, Junita Monika. dan Haryani, Nanik Suryo (LAPAN, 2015)
The high human activity in the mining and industrial areas increase the potency for hazardous and toxic waste pollution. One form of hazardous and toxic waste is acid sludge, a mixture of hydrocarbons and sulfuric acid derived from the disposal of plant wax. This study aims is to detect and monitor the acid sludge contaminated area based o the Land Surface Temperature (LST) derived from Landsat 7 ETM multi temporal data.